The Future of Xi's china Scenarios and Implications for Europe - Amighini, Alessia (ISPI Publications, 2022)
At the upcoming 20th Party Congress, which opens Sunday in China, Xi Jinping is expected to be confirmed as the country's Secretary General for an unprecedented third term. At a time of international instability caused by the Covid pandemic and the war in Ukraine, as well as rising competition between international superpowers, the Chinese leadership is called to increase the country's international standing, while ensuring economic growth at the domestic level. However, achieving these goals will not be without challenges. This Report analyses China's hard road to international prestige and development. Which prospects for China's economic growth? Which obstacles to its rise at the global level? To which extent can the Party steer the country's direction?